Comparison of Automated Office Blood Pressure With Office and Out-Off-Office Measurement Techniques: A Systematic Review and Meta-Analysis. Issue 2 (February 2019) - Pappaccogli, Marco; Di Monaco, Silvia; Perlo, Elisa; Burrello, Jacopo; D'Ascenzo, Fabrizio; Veglio, Franco; Monticone, Silvia; Rabbia, Franco
Abstract : Automated office blood pressure (AOBP) has emerged as a valuable tool to assess patient's BP status, but the lack of strong evidence to establish a threshold value for hypertension diagnosis limits its use in clinical practice. We aimed at synthesizing the published literature through a meta-analysis of studies comparing AOBP with other BP measurement techniques and at analyzing the differences between AOBP and physician's office BP, nonphysician's office BP, daytime ambulatory BP monitoring, and home BP monitoring. We searched PubMed database for articles published up to April 2018; eligible studies compared AOBP with office and out-of-office measurement techniques and reported the BP differences or BP values obtained. Twenty-six studies, for a total of 7116 patients, were included in the analysis. AOBP values were lower than physician (systolic BP, −10.48 mm Hg; 95% CI, −13.15 to −7.81/diastolic BP, −4.44 mm Hg; 95% CI, −6.07 to −2.80) and nonphysician office ones (systolic BP, −6.89 mm Hg; 95% CI, −8.75 to −5.04/diastolic BP −3.82 mm Hg; 95% CI, −4.86 to −2.78). No significant differences were found between AOBP and daytime ambulatory BP monitoring (systolic BP, −1.85; 95% CI, −4.50 to 0.79/diastolic BP, 0.12; 95% CI, −1.42 to 1.66) and home BP monitoring (systolic BP, −2.65; 95% CI, −8.42 to 3.12/diastolic BP, −1.67; 95% CI, −4.20 to 0.87). AOBP readings did not differ significantly from out-of-office blood pressure, still remaining an office technique; it may improve hypertension diagnosis by overcoming some of office BP limitations, including the white coat effect. Abstract : Supplemental Digital Content is available in the text.